The Effect of Local Revenue, Capital Expenditure, and Expenditure on Education and Health Functions on the Poverty Rate: A Study in Regencies/Cities in East Nusa Tenggara (NTT) from 2019–2024 - Ardiyanto Maksimilianus Gai; Gaguk Apriyanto Apriyanto; Moh. Burhan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The objective of this study is to determine the effect of local revenue, capital expenditure and education and health function expenditure on the poverty rate: a study conducted in regencies/cities within East Nusa Tenggara (NTT) Province for the period 2019–2024. The type of research applied in this study is correlational research, and its scope refers to quantitative research. The research location refers to the place where the research data is obtained. In this case, the location is the regencies/cities in East Nusa Tenggara (NTT), with data collected from regional financial reports for the years 2019–2024. The type of data used in this study is secondary data, specifically time series data. The data collection techniques employed in this research consist of two primary methods: literature study and documentation method. The data analysis technique used is multiple linear regression. Based on the research findings, three main conclusions were obtained local revenue has a significant and negative effect on the poverty rate, capital expenditure does not have a significant effect on the poverty rate, and expenditure on education and health functions has a significant and negative effect on the poverty rate. Based on the study’s findings, future research should consider additional variables such as social assistance, unemployment, and inflation to better understand poverty dynamics in east nusa tenggara. Using panel data or qualitative approaches, expanding the study area, and evaluating the efficiency of education and health spending are also recommended for more accurate and region-specific poverty reduction insights.